Experimental study of sodium silicate and potassium hydroxide solutions and mixing temperature on setting time and compressive strength of the geopolymer mortar - Hadi Nazarpour (Iranian Society of Structrual Engineering (ISSE), 2020)
Geopolymers have attracted the attention of many researchers in recent years as a non-cement concrete. Instead of cement, various material such as metakaoline, zeolite, rice husk ash, etc are used in Geopolymers. In order to complete the geopolymerization process, a binder is used along with the selected material from the chemical solutions. Preparation of chemical solutions usually liberates a lot of heat. In this research, steel slag was used as a substitute for cement. In addition, solutions of sodium silicate and potassium hydroxide used as chemical solutions. This research evaluates the effects of chemicals and the mixing temperature on properties of geopolymer mortar. For this purpose, 20 different mixing ratios were made. Setting time, mixture temperature, elasticity module and compressive strength of sample were measured. The results showed that the higher the amount of chemicals solution creates mores mixing temperature and compressive strength and less setting time. Between solutions of sodium silicate and potassium hydroxide, the effects of increasing of the sodium silicate solution are greater in strength growth, temperature growth and setting time reduction. The electron microscopic images of the samples with the highest and the least strength showed that the higher amount of chemicals and the temperature of the construction caused the formation of more hardened geopolymer gel and the width of the cracks observed in the mix design with less chemical solutions It is nearly 3 times more. In addition, X-ray radiation testing for the samples with the highest and lowest strenght showed that the intensity of reflection in the sample with lower strenght was higher; indicating that the hardened geopolymer gel was less due to the reduction of chemical concentration.